An exploration of machine learning methods for robust boredom classification using EEG and GSR data - Seo, Jungryul; Laine, Teemu H.; Sohn, Kyung Ah (Sensors (Switzerland), 2019)
In recent years, affective computing has been actively researched to provide a higher level of emotion-awareness. Numerous studies have been conducted to detect the user’s emotions from physiological data. Among a myriad of target emotions, boredom, in particular, has been suggested to cause not only medical issues but also challenges in various facets of daily life. However, to the best of our knowledge, no previous studies have used electroencephalography (EEG) and galvanic skin response (GSR) together for boredom classification, although these data have potential features for emotion classification. To investigate the combined effect of these features on boredom classification, we collected EEG and GSR data from 28 participants using off-the-shelf sensors. During data acquisition, we used a set of stimuli comprising a video clip designed to elicit boredom and two other video clips of entertaining content. The collected samples were labeled based on the participants’ questionnaire-based testimonies on experienced boredom levels. Using the collected data, we initially trained 30 models with 19 machine learning algorithms and selected the top three candidate classifiers. After tuning the hyperparameters, we validated the final models through 1000 iterations of 10-fold cross validation to increase the robustness of the test results. Our results indicated that a Multilayer Perceptron model performed the best with a mean accuracy of 79.98% (AUC: 0.781). It also revealed the correlation between boredom and the combined features of EEG and GSR. These results can be useful for building accurate affective computing systems and understanding the physiological properties of boredom.
Keywords: 10-fold cross-validation; Affective Computing; Boredom; Emotion; Emotion classification; Galvanic skin response; Machine learning methods; Physiological properties; Adult; Area Under Curve; Boredom; Discriminant Analysis; Electroencephalography; Female; Galvanic Skin Response; Humans; Machine Learning; Male; ROC Curve; Surveys and Questionnaires; Young Adult; Boredom; Classification; EEG; Emotion; GSR; Machine learning; Sensor